The Role of Teachers in Increasing Students’ Creativity and Learning Activeness in Civic Education Subject Subject Subject of Class X MIPA 2 SMAN 16 Bone Learning - Ilham, Ilham; Ridha, Rasyid; Rahma, Aulia; Rusdi, Muhammad (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This reseach aims to determine the role of teachers in increasing students’ creativity and active learnig Class X MIPA 2 SMAN 16 Bone. The type of reseach used is a qualitive reseach are oservation, interviews and document study in which the autor directly sees the situation in the field. The results of this research show that the role of teachers in increasing students' creativity and active learning is that teachers and students are always active in reading, teachers give appreciation for the results of students' creativity, involve students in determinin goals and evaluations and always involve students in active and creative learning. Increasing students creativity and active learning, namely teachers provide assignments that suit students needs so that they are able to increase creativity and activeness according to student abilities.